Improve Community Income Through Community Empowerment Programs Joint Business Group (Kube) in Dumati Village, Telaga Biru District - Rusli Isa (AIBPM Publisher, 2019)
This study aims to describe: 1) the KUBE Bintang Terang Program, 2) the role of KUBE in increasing community income, the success of the KUBE Bintang Terang program, 3) supporting and inhibiting factors for the implementation of the KUBE Bintang Terang program. This research use desciptive qualitative approach. The research subjects were managers and members of the KUBE program. Data analysis techniques used are data reduction, data presentation, and conclusion. Triangulation used is source triangulation and technique. The results of the study show that: 1) the KUBE program is a group / place for learning to obtain knowledge and skills and get the opportunity through activities in making embroidery clothes and beautiful brooches. 2) The role of KUBE in binding community income is a benchmark for KUBE programs. 3) The success of the KUBE program to be able to increase income and family welfare which is characterized by increasing members' income, social relations are well established. 4) Factors supporting the establishment of cooperation between managers, members, suppliers of raw materials, markets, government, the motivation for entrepreneurship, maintaining trust and market demand. The inhibiting factor is the lack of capital, sometimes there are unfavorable relationships between members, giving rise to a sense of boredom, lack of market demand in certain months and the number of competitors. The recommendation for the KUBE Bintang Terang program is to hold regular meetings, increase capital, and carry out promotions to areas that have not been reached. Keywords: Community Empowerment, KUBE, Community Income